Interaction of discrete breathers with thermal fluctuations - Eleftheriou, M.; Flach, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Discrete breathers (DB) are time-periodic and spatially localized lattice excitations, which can be linearly stable or unstable with respect to either localized or extended perturbations. We analyze the interactionof DBs with a thermalized background of small amplitude lattice excitations in a one-dimensional lattice of Morse oscillators with nearest neighbour interaction. We find that stable DBs are barely influenced by the thermal noise. Unstable DBs are starting to propagate through the lattice, without loosing their localization character. The instability can be both due to localized perturbations, as well as due to extended perturbations. We discuss these observations in terms of resonances of DBs with localized and delocalized perturbations, and relate them to the issue of DB impact on statistical properties of nonlinear lattices.